Earth Revealing; Earth Healing: Ecology and Christian Theology - Edwards, Denis (Liturgical Press, 2001)
Titlepage -- Copyright -- Contents -- List of Illustrations -- Acknowledgments -- Introduction -- Contributors -- 1 The Landscape Tradition: A Broader Vision for Ecotheology -- 2 Globalization and Ecology -- 3 "For Your Immortal Spirit Is in All Things": The Role of the Spirit in Creation -- 4 Enfleshing the Human: An Earth-Revealing, Earth-Healing Christology -- 5 God's Shattering Otherness: The Trinity and Earth's Healing -- 6 Embracing Unloveliness: Exploring Theology from the Dungheap -- 7 Up Close and Personal: In the End, Matter Matters